Поняття та ознаки соціального страхування від нещасних випадків та професійних захворювань на виробництві - Сорока, Олена Павлівна; Сорока, О. П.; Soroka, Olena P.; Soroka, O. P. (Одеса : Гельветика, 2020)
У статті розглянуто поняття та характерні ознаки, притаманні загальнообов’язковому державному соціальному страхуванню від нещасних випадків та професійних захворювань на виробництві. Проаналізувавши наукові підходи, законодавче регламентування, категорію «загальнообов’язкове державне соціальне страхування від нещасних випадків та професійних захворювань на виробництві» запропоновано визначити як установлену і регламентовану державою систему гарантій, що передбачає матеріальне забезпечення, страхові виплати та надання соціальних послуг застрахованій особі в разі настання нещасного випадку та професійного захворювання на виробництві в процесі виконання такою особою своїх трудових обов’язків або пов’язаних із трудовими. До характерних ознак такого страхування віднесено такі: (а) є певним захистом від настання небажаних ризиків чи наслідків; (б) є гарантією закріпленого в ст. 46 Конституції України права на соціальний захист; (в) є державним страхуванням, тобто порядок, умови здійснення визначаються і регулюються державою та не можуть змінюватися на розсуд сторін, як це може бути в приватному; (г) охоплює конкретну сферу, а саме трудову діяльність. Страхування від нещасних випадків та професійних захворювань на виробництві невіддільне від трудової діяльності та може здійснюватися лише у разі впливу на працівника небезпечного виробничого фактору чи середовища, що сталися у процесі виконання ним трудових обов’язків або пов’язаних із трудовими, унаслідок яких заподіяно шкоду здоров’ю або настала смерть; (ґ) переслідує певну економічну функцію, що полягає у створенні необхідних умов для відтворення трудових ресурсів; (д) обов’язковість, тобто особи, які визначені законом, повинні сплачувати внески на загальнообов’язкове соціальне страхування; (е) імовірний характер відносин, який передбачає неможливість визначення заздалегідь суб’єктного складу правовідносин, часу настання випадку, розміру виплат.

The article considers the concepts and characteristics inherent in the mandatory state social insurance against accidents and occupational diseases at work. After analyzing scientific approaches, the legislation regulating the category of “compulsory state social insurance against accidents and occupational diseases at work” is defined as a system of guarantees established and regulated by the state, which provides material support, insurance payments and social services to the insured person in case of accident. case and occupational disease at work in the process of such person’s performance of their duties or related to labor. The characteristic features of such insurance include the following: (a) there is some protection against the occurrence of undesirable risks or consequences; (b) is a guarantee enshrined in Art. 46 of the Constitution of Ukraine, the right to social protection; (c) is public insurance, ie the procedure, conditions of implementation are determined and regulated by the state and may not be changed at the discretion of the parties, as it may be in private; (d) covers a specific area, namely employment. Insurance against accidents and occupational diseases at work is inseparable from work and can be carried out only in the case of exposure of the employee to a dangerous production factor or environment that occurred in the course of his duties or related to work, resulting in harm to health. or death; (e) pursues a certain economic function, which is to create the necessary conditions for the reproduction of labor resources; (f) compulsory, ie persons required by law to pay contributions to compulsory social insurance; (g) the probable nature of the relationship, which implies the impossibility of determining in advance the subjective composition of the legal relationship, the time of the case, the amount of payments.

The article considers the concepts and characteristics inherent in the mandatory state social insurance against accidents and occupational diseases at work. After analyzing scientific approaches, the legislation regulating the category of “compulsory state social insurance against accidents and occupational diseases at work” is defined as a system of guarantees established and regulated by the state, which provides material support, insurance payments and social services to the insured person in case of accident. case and occupational disease at work in the process of such person’s performance of their duties or related to labor. The characteristic features of such insurance include the following: (a) there is some protection against the occurrence of undesirable risks or consequences; (b) is a guarantee enshrined in Art. 46 of the Constitution of Ukraine, the right to social protection; (c) is public insurance, ie the procedure, conditions of implementation are determined and regulated by the state and may not be changed at the discretion of the parties, as it may be in private; (d) covers a specific area, namely employment. Insurance against accidents and occupational diseases at work is inseparable from work and can be carried out only in the case of exposure of the employee to a dangerous production factor or environment that occurred in the course of his duties or related to work, resulting in harm to health. or death; (e) pursues a certain economic function, which is to create the necessary conditions for the reproduction of labor resources; (f) compulsory, ie persons required by law to pay contributions to compulsory social insurance; (g) the probable nature of the relationship, which implies the impossibility of determining in advance the subjective composition of the legal relationship, the time of the case, the amount of payments.
Сорока О. П. Поняття та ознаки соціального страхування від нещасних випадків та професійних захворювань на виробництві / О. П. Сорока // Юридичний вісник. - Одеса : Гельветика - 2020. - № 3. - С. 363-368.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; social protection; insurance; labor activity; insured event; insurance risk; accident; occupational disease; соціальний захист; страхування; трудова діяльність; страховий випадок; страховий ризик; нещасний випадок; професійне захворювання